Spin excitations and the Fermi surface of superconducting FeS - Haoran Man (Nature Portfolio, 2017)
Condensed Matter Physics: nematic order does not exist in FeS Low energy spin excitations show no sign of nematic order existing in FeS, a structure-similar material of FeSe, without direct coupling to superconductivity. An international team led by Pengcheng Dai at the Rice University and Beijing Normal University carried out transport, neutron scattering, quantum oscillation measurements combined with theoretical calculations to study single crystals of FeS. They found that the spin excitations below 100 meV reveal only stripe-type spin fluctuations without direct coupling to superconductivity, suggesting FeS being a tetragonal paramagnet without nematic order and with a reduced quasiparticle mass compared to that of FeSe. These results not only suggest that FeS is a weakly correlated analog of FeSe, but also shed a light to understand the nematic order in FeSe, which is due to the competing spin fluctuations driven by frustrated magnetic interactions.